2012
DOI: 10.5558/tfc2012-099
|View full text |Cite
|
Sign up to set email alerts
|

Community forest organizations and adaptation to climate change in British Columbia

Abstract: The effects of climate change in many regions are expected to be significant, and likely to have a detrimental effect on the health of forests and the communities that often depend on those forests. At the same time climate change presents a challenge as it requires changes in both forest management, and the institutions and policies developed that govern forest management. In this paper, we report on a study assessing how Community Forests Organizations (CFOs) in British Columbia (BC), which were developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
7
1
4
Order By: Relevance
“…A further literature search through Scopus using keywords such as 'adaptation', 'forests', 'owners' and 'climate change' produces papers that largely focus on modelling and longterm experiments (D'Amato et al 2011;Duncker et al 2012;Fürstenau et al 2007;Ge et al 2013;Mason et al 2012;Yousefpour et al 2010). It also illustrates recommended management changes for adaptation, including diversification of species and structure, choice of species adapted to emerging conditions (particularly drought), increased complexity and management intensity, regional multi-ownership planning, and increased monitoring (D'Amato et al 2011;Furness and Nelson 2012;Kolström et al 2011;Mason et al 2012;Spies et al 2010;Temperli et al 2012). Only very few studies focus on the attitudes and practices of the owners towards climate change and ask to what extent is adaptation taking place.…”
Section: Private Forest Owners and Climate Change Adaptation Policymentioning
confidence: 99%
See 1 more Smart Citation
“…A further literature search through Scopus using keywords such as 'adaptation', 'forests', 'owners' and 'climate change' produces papers that largely focus on modelling and longterm experiments (D'Amato et al 2011;Duncker et al 2012;Fürstenau et al 2007;Ge et al 2013;Mason et al 2012;Yousefpour et al 2010). It also illustrates recommended management changes for adaptation, including diversification of species and structure, choice of species adapted to emerging conditions (particularly drought), increased complexity and management intensity, regional multi-ownership planning, and increased monitoring (D'Amato et al 2011;Furness and Nelson 2012;Kolström et al 2011;Mason et al 2012;Spies et al 2010;Temperli et al 2012). Only very few studies focus on the attitudes and practices of the owners towards climate change and ask to what extent is adaptation taking place.…”
Section: Private Forest Owners and Climate Change Adaptation Policymentioning
confidence: 99%
“…A wider survey covering Germany, Sweden and Portugal shows that an individual's strength of belief in climate change will often influence their willingness and capacity to adapt (Blennow et al 2012). In Canada, Furness and Nelson (2012) surveyed 38 member organisations of the British Columbia Community Forest Association and found that 32 % were already incorporating adaptation strategies into their management while 45 % were currently researching adaptation. Those who were engaged or interested in adaptation were more likely to be concerned about global climate change and had observed or expected to see impacts of climate change.…”
Section: Private Forest Owners and Climate Change Adaptation Policymentioning
confidence: 99%
“…An analysis of 38 community forestry organisations in British Columbia found that 45 % were researching adaptation and 32 % were integrating adaptation techniques into their work (Furness and Nelson 2012). Whilst these community forest managers appreciated support and advice from government for adaptation, balancing this advice with autonomy for communities to make their own decisions was considered challenging.…”
Section: Adaptation Actions At Different Management Levelsmentioning
confidence: 99%
“…Hasonlókép-pen a klíma bizonytalanság, illetve -kockázatok eltérő felfogásaira, adaptációban játszott szerepére mutatott rá Nagy-Britannia-szerte Petr et al (2014). Furness & Nelson (2012) Kanadában, British Columbiában kutatták az érzékelés és a válaszadás kérdését, helyi kö-zösségi erdészeti szervezetek kérdőíves vizsgálatával, ugyanitt készült Nelson et al (2016) tanulmánya, amely az erdészeti szakemberek adaptációs hajlandóságát elemezte. Lenart & Jones (2014) pedig a klímaváltozásba vetett hit szerepét vizsgálta a cselekvési hajlandó-ságban az USA-ban, kimutatva az összefüggést.…”
Section: Szakirodalmi áTtekintésunclassified
“…Nyilván ez az eredmény meglehetősen ország-specifikus, más helyszíneken eltérő eredmények adódtak (vö. Furness & Nelson 2012;Detten & Faber 2013;Sousa-Silva et al 2016) A módszertanban jelzett háromféle erdő-csoportosításban a válaszadók átlagos klíma-romlás-indexét a 2. ábra mutatja. Ez jelzi már azt, hogy a legnagyobb különbségek a regionális és az erdőtípus szerinti bontásban mutatkoztak, ezeket érdemes hát közelebbről is megvizsgálni, amikor az érzékelés és a hely kapcsolatát vizsgáljuk, hiszen a domborzati típusok kapcsán a hegyvidékekre és a síkvidé-kekre is számos esetben igaz, hogy valamelyest kisebb mértékben tapasztalják a problémá-kat.…”
Section: Az éGhajlatváltozás éRzékeléseunclassified